SOSIALISASI APLIKASI MERDEKA MENGAJAR DAN PENGENALAN PLATFORM SIMBA DALAM MENINGKATKAN PEMAHAMAN MEDIA PEMBELAJARAN KEPADA TENAGA PENDIDIK DI SMPN 10 CILEGON - Dewi Surani; Aas Nur Asnawati; Asensa Widia Kusuma (LPPM Universitas Bina Bangsa, 2022)
The Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) has made the Merdeka Mengajar application on Merdeka Belajar Episode 15. This stage is an application that can uphold educators in carrying out the Independent Education program. In accordance with the Minister of Education and Culture, Nadiem Makarim, in making the Merdeka Education curriculum and the Merdeka Teaching application on February 11, 2022, the Merdeka Mengajar application is an application for educators that will be formed into an application that is not only material content and services, but is actually owned by teachers, from teachers, for teachers. So, here's an app to implement a free education plan and look for ways to improve as an instructor,